The Reality of Code-Mixing in Nadzom Batu Ngompal - Moh. Irfan; Herman Wijaya; Nunung Supratmi; Ramlah H.A. (SeBaSa)
The code mix used in the Tajwid Nazom Batu Ngompal book is a distinct characteristic that makes the book unique and interesting. The book is presented in the form of rhymes so that the mixed code has a function as rhyme poems in rhymes. The method used in this research is descriptive qualitative. The data from this research are verbal data in the form of writing. The data source is derived from archives or documents, namely the book of Tajwid Nazom Batu Ngompal. Research data in the form of writings in the form of mixed code use. Data collection is carried out by studying archives or documents, take notes. Data were analyzed using interactive analysis techniques. Based on the results of data analysis collected from the book of Tajwid Nazom Batu Ngompal in the form of mixed language codes that are used in the form of good verbs, adjectives, nouns, phrases, clauses, repetitions and idioms. The dominant form of code mixing used in the book is mixed code of nouns and adjectives.